2017
DOI: 10.1177/0047287517714907
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Work-Related Smartphone Use on Vacation: An Exploratory Study of Taiwanese Tourists

Abstract: Given the proliferation of smartphone use, more and more people feel obligated to stay connected to work during evening hours, weekends, or vacations. Therefore, building on work–family border theory (Clark 2000), which suggests the blending of work and nonwork domains can result in work–family interference, this study investigated the potential problems of work-related smartphone use on vacation. Derived from a sample of 500 Taiwanese smartphone users, results revealed that nearly 40% of respondents used thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 64 publications
0
35
2
Order By: Relevance
“…A few recent studies have explored emotions and motivations among DFT tourists ( Cai et al, 2019 ; Fan et al, 2019 ; Floros et al, 2019 ). Tourists' emotional responses to DFT are distributed on a spectrum form being anxious to relaxed, depending on particular travel intentions, destination environments, and daily ICT use behaviours ( Cai et al, 2019 ; Chen et al, 2018 ; Hoving, 2017 ; Upadhyay & Mishra, 2017 ). Motivations to unplug on holiday have also been considered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A few recent studies have explored emotions and motivations among DFT tourists ( Cai et al, 2019 ; Fan et al, 2019 ; Floros et al, 2019 ). Tourists' emotional responses to DFT are distributed on a spectrum form being anxious to relaxed, depending on particular travel intentions, destination environments, and daily ICT use behaviours ( Cai et al, 2019 ; Chen et al, 2018 ; Hoving, 2017 ; Upadhyay & Mishra, 2017 ). Motivations to unplug on holiday have also been considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, escape, personal growth, health and well-being, and improved relationships have been identified as important factors driving tourists to get off-line ( Egger et al, 2020 ). In one study, 12% of Taiwanese tourists did not take or use smartphones in their most recent travels; and 50% avoided distant work communications ( Chen et al, 2018 ). In a Netherlands study, Hoving (2017) found some Dutch holidaymakers selectively rejected electronic devices or mindfully disconnected during the whole holiday time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The tourist satisfaction factor determines the sustainability of the tourism industry. The following research states that the importance of tourist satisfaction in supporting the sustainability of the tourism industry (Del Bosque and San Martín, 2008;Hasegawa, 2010;Sukiman et al, 2013;Yürük et al, 2017;Chen et al, 2018;Silaban et al, 2019). The research hypothesis is stated as: H3: Tourists' satisfaction positively and significantly influences revisit intention.…”
Section: Tourists' Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…They almost use this device all of the day and always check it every now and then (Persaud and Azhar, 2012). Chen et al (2017) reported that all people regularly use these phones in every activity in their lives. Regan and Chang (2015) defined smart phones as a pocket mobile phone but with stronger capabilities, with large screen, easily internet access and location based support.…”
Section: Smart Phone Technologymentioning
confidence: 99%